RNA Polymerase, a Scrunching Machine - Roberts, Jeffrey W. (Science (American Association for the Advancement of Science), 2006)
Recent research illuminates the initial steps of making an RNA chain by showing how the energy of nucleoside triphosphate hydrolysis is captured to break the enzyme loose from its tight contact with DNA. RNA polymerase stores energy to break its initial bonds with DNA by scrunching the single strands of DNA that were unwound in the region where the polymerase started RNA synthesis.